Deformation and Fracture Behavior of Sandwiched Copper Foam Brazed Joint Using Amorphous Copper–Tin–Nickel–Phosphorus Filler - Mohd Zahri, Nur Amirah; Yusof, Farazila; Badruddin, Irfan Anjum; Haseeb, A. S. Md. Abdul; Sukiman, Nazatul Liana; Kamangar, Sarfaraz (Frontiers in Materials, 2021)
Utilization of open-cell metal foams in functional applications such as in energy absorption, noise absorber, heat insulator and lightweight panels become trending in many industrial application. The development of reliable joining technologies for sandwiched metal foams is crucial for heat e application and one of the technique used is brazing process. In current work, copper foam was sandwiched between copper plate using amorphous filler of Cu-9.7Sn-5.7Ni-7.0P (Cu-copper, Sn-tin, Ni-nickel, P-phosphorus) via brazing technique. The shear test was conducted on the brazed joint interface of copper/copper foam, while the compressive test was carried out on the brazed sample. Microstructures of the copper substrate surface obtained from the shear-fracture of brazed copper/copper foam show tear region and cleavage fractures. The stress-strain curve of shear and compressive explain the deformation behavior of the brazed sample.